2019
DOI: 10.12688/wellcomeopenres.15066.1
|View full text |Cite
|
Sign up to set email alerts
|

Spo13 prevents premature cohesin cleavage during meiosis

Abstract: Meiosis produces gametes through two successive nuclear Background: divisions, meiosis I and meiosis II. In contrast to mitosis and meiosis II, where sister chromatids are segregated, during meiosis I, homologous chromosomes are segregated. This requires the monopolar attachment of sister kinetochores and the loss of cohesion from chromosome arms, but not centromeres, during meiosis I. The establishment of both sister kinetochore mono-orientation and cohesin protection rely on the budding yeast meiosis I-speci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“… The mass spectrometry proteomics data have been deposited to the ProteomeXchange Consortium via the PRIDE partner repository. This study PXD012627 Experimental Models: Organisms/Strains Yeast strains used in this study n/a See Table S1 Oligonucleotides Oligonucleotides used in this study for qPCR n/a See Table S3 Recombinant DNA Plasmids generated in this study n/a See Table S2 Software Image J plugin “DV_DotCounter” for analysis of microscopy data is available on Github This study and Galander et al., 2019 https://doi.org/10.5281/zenodo.2553082 ) Image J plugin “YeastLineProfiler” for analysis of microscopy data is available on Github This study and Galander et al., 2019 https://doi.org/10.5281/zenodo.2560099 Other NEXTflex-6 DNA Barcodes Perkin Elmer 514101 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… The mass spectrometry proteomics data have been deposited to the ProteomeXchange Consortium via the PRIDE partner repository. This study PXD012627 Experimental Models: Organisms/Strains Yeast strains used in this study n/a See Table S1 Oligonucleotides Oligonucleotides used in this study for qPCR n/a See Table S3 Recombinant DNA Plasmids generated in this study n/a See Table S2 Software Image J plugin “DV_DotCounter” for analysis of microscopy data is available on Github This study and Galander et al., 2019 https://doi.org/10.5281/zenodo.2553082 ) Image J plugin “YeastLineProfiler” for analysis of microscopy data is available on Github This study and Galander et al., 2019 https://doi.org/10.5281/zenodo.2560099 Other NEXTflex-6 DNA Barcodes Perkin Elmer 514101 …”
Section: Methodsmentioning
confidence: 99%
“…An attractive candidate is the budding yeast meiosis-I-specific Spo13 protein. Cells lacking SPO13 undergo a single meiotic division, show monoorientation defects, and fail to protect cohesin ( Katis et al., 2004b , Klapholz and Esposito, 1980 , Lee et al., 2004 , Shonn et al., 2002 , Galander et al., 2019 ). Accordingly, Spo13 is required for monopolin localization at kinetochores ( Katis et al., 2004b , Lee et al., 2004 ) and is implicated in ensuring the proper pericentromeric localization of Sgo1 ( Kiburz et al., 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 48–51 ] There, PP2A is thought to dephosphorylate cohesin, thus preventing its cleavage by separase. Artificial tethering of PP2A to arm cohesin in fission yeast [ 51 ] or budding yeast [ 52 ] impairs cohesin cleavage on chromosome arms, highlighting the importance of restricting PP2A activity to the pericentromere. Thus, cohesin protection in the pericentromere requires the careful balancing of cohesin‐directed kinase and phosphatase activity; disruption of this balance is likely to interfere with the maintenance of pericentromeric cohesin after metaphase I.…”
Section: Mokirs Regulate Cohesin Kinases and Shugoshin To Promote Cohmentioning
confidence: 99%
“…spo13Δ mutants, for example, only undergo a single meiotic division [ 82 ] characterized by a mixture of reductional and equational chromosome segregation. [ 52,53 ] This phenotype is not seen in fission yeast moa1Δ cells [ 10 ] or mouse Meikin −/− oocytes. [ 15 ] Little is known about the molecular basis of the altered cell cycle in spo13Δ cells, but it has been observed that deletion of the spindle checkpoint component MAD2 restores the second division in a majority of spo13Δ cells, [ 53 ] although chromosome segregation is still defective in spo13Δ mad2Δ strains.…”
Section: Mokirs Perform Specialized Functions In Budding Yeast and Drmentioning
confidence: 99%
“…including Cdc5, in pericentromeric regions (Galander et al, 2019). It may also 12 prevent Cdc5-driven MutLg activation in these regions.…”
mentioning
confidence: 99%